Transdiagnostic cognitive behavioural therapy (CBT): case reports from Saudi Arabia. (December 2014) - Alatiq, Yousra
Abstract: Transdiagnostic cognitive behavioural therapy (CBT) focuses on the processes shared across disorders and can be applied to a wide range of mental health problems or comorbid conditions. The transdiagnostic approach provides the potential opportunity to improve access to CBT, particularly in countries such as Saudi Arabia, where the number of well-trained therapists is limited. This study aims to examine the feasibility and potential benefit of transdiagnostic CBT for Saudi patients. Case reports describe the outcome of transdiagnostic CBT for four female patients who presented a wide range of symptoms and conditions without conducting any specific diagnostic assessments. The results support the positive effect of this treatment method on depression, anxiety symptoms, and general functioning. Patient feedback and observable improvements also supported these outcomes. However, the results are limited by the small sample size and simple study design. Transdiagnostic CBT is a feasible treatment approach for patients in Saudi Arabia. However, to confirm this preliminary finding, more studies are required.